Analisis Pengaruh Corporate Social Responbility Terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Pemoderasi - Aditya, Putu Ferlly; Haninun (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Corporate social responsibility now plays a very central role in the operations of business entities. To realize sustainable development, companies must holistically consider economic, social, and environmental aspects. This research aims to examine the impact of Corporate Social Responsibility on company financial performance, as well as investigate the influence of profitability as a moderating factor on this relationship. This research uses a purposive sampling method in taking samples and collecting data through documentation and literature study. Data analysis involved the following steps: first, descriptive statistical analysis; second, classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroscedasticity tests; third, multiple linear regression analysis; and fourth, hypothesis testing, which includes the coefficient of determination (R2), F test, T test, and moderation regression analysis. Research results show that corporate social responsibility has a significant impact on company value, especially in food and beverage companies listed on the Indonesia Stock Exchange in the period 2018- 2020. Furthermore, the results of moderated regression analysis show that profitability significantly moderates the relationship between corporate social responsibility and corporate value, with a significance value of 0.000, indicating that profitability Profit plays an important role in adjusting the impact of corporate social responsibility on businesses value.